Bicomponent ZnO-Ag janus nanoparticles with high antitumor activity in vitro - O. V. Bakina; V. R. Zhou; M. I. Lerner (Сибирский онкологический журнал, 2023)
Background. Nanoparticles (NPs) of zinc and silver oxide are promising antitumor agents, the use of which can enhance modern approaches to cancer treatment. Using bicomponent ZnO-Ag nanoparticles, one can increase the efficiency due to the occurrence of a synergistic antitumor effect. Among the main physicochemical properties that affect the antitumor activity of nanoparticles, one can distinguish their size and distribution of components inside the particle or their microstructure, however, these aspects are currently poorly understood.The aim of this study is the synthesis of ZnO-Ag nanoparticles using electrical explosive of wire technology and the in vitro study of the antitumor activity of NPs against breast ductal adenocarcinoma MCF-7 (ATCC HTB-22) and the HeLa cell line isolated from a cervical tumor.Material and Methods. ZnO-Ag nanoparticles were obtained by simultaneous electric explosion of zinc and silver twisted wires in a gas mixing atmosphere: argon and oxygen. The content of the components was regulated by varying the wire diameters. Physicochemical properties were studied using X-ray phase analysis, thermal desorption of nitrogen, and transmission electron microscopy. Antitumor activity in vitro was studied using the MTT test against HeLa and MCF-7 cell lines.Results. As a result of an electric explosion of twisted wires in an argon + oxygen gas mixture, ZnO-Ag NPs with different contents of components and the structure of Janus nanoparticles were obtained. The study of the physicochemical properties of nanoparticles showed that an increase in the silver content led to a decrease in the average particle size, an increase in their specific surface area, an increase in their photochemical activity and the ability to generate reactive oxygen species. The high antitumor activity of nanoparticles with a minimum silver content can be explained by a decrease in the size of silver fragments from 46 nm to 23 nm and a decrease in the average particle size from 92 nm to 54 nm. A decrease in the size of NPs and their components contributes to an increase in their solubility and, accordingly, cytotoxicity. In addition, a decrease in the size of crystallites makes it possible to increase the number and length of the ZnO-Ag interface.Conclusion. In the present study, bicomponent ZnO–Ag NPs were synthesized using the joint electric explosion of zinc and silver wires in a mixed atmosphere of argon and oxygen. A study of the physicochemical properties of nanoparticles was carried out and it was found that they all have the structure of Janus nanoparticles, an average size of 54 to 92 nm, and photochemical activity and the ability to generate ROS. Using the MTT test, the antitumor activity of NPs was confrmed using MCF-7 and HeLa cell lines. The high effciency of ZnO-Ag NPs containing 20% wt. silver indicates the possibility of using these NPs in antitumor therapy.